2020
DOI: 10.1007/s00134-019-05890-w
|View full text |Cite|
|
Sign up to set email alerts
|

Ventilator-associated pneumonia caused by multidrug-resistant Gram-negative bacteria: understanding nebulization of aminoglycosides and colistin

Abstract: The use of nebulized antibiotics for treating ventilatorassociated pneumonia (VAP) caused by multidrugresistant (MDR) Gram-negative bacteria (GNB) increases worldwide. There is a paradox, however, between the large body of experimental evidence supporting the administration of nebulized rather than intravenous aminoglycosides and colistin to treat inoculation pneumonia caused by GNB [1, 2], and the paucity of clinical studies confirming such a benefit in VAP. Based on the recommendations of the European Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…The VMN was placed at the dry side of the humidifier. A lung protective, low tidal volume ventilation strategy of 8 mL/Kg for a 69 Kg adult was adopted (Vt 550 mL, RR 13 BPM, and I:E Ratio 1:2) [ 64 ]. The capture filter was placed between the endotracheal tube (ETT) (Flexicare, 8.00 mm, UK) and a test lung (IMT Medical, Bachs Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The VMN was placed at the dry side of the humidifier. A lung protective, low tidal volume ventilation strategy of 8 mL/Kg for a 69 Kg adult was adopted (Vt 550 mL, RR 13 BPM, and I:E Ratio 1:2) [ 64 ]. The capture filter was placed between the endotracheal tube (ETT) (Flexicare, 8.00 mm, UK) and a test lung (IMT Medical, Bachs Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…These very high doses were based on studies performed in 2008-2010 in anesthetized and mechanically ventilated piglets whose lungs were infected by the bronchial inoculation with high concentrations of P. aeruginosa [42]. The nebulization of 100,000 IU/kg of CMS could eradicate the causative microorganism from 67% of the infected pulmonary segments within 24 h. These very high doses are actually recommended [43]. In 2018, a meta-analysis performed on 12 studies published between 2005 and 2016 [15,18,19,22,[26][27][28][32][33][34]36,37] reported the effectiveness of nebulized CMS as a monotherapy for treating respiratory tract infections caused by MDR and/or CMS only susceptible GNB [44].…”
Section: Treatment Of Mdr Gnb Ventilator-associated Pneumoniamentioning
confidence: 99%
“…Optimizing lung deposition of CMS to provide effective bacterial killing in critically ill patients with VAP and VAT requires a specific nebulization strategy including [43,53,94]: (1) the preferential use of vibrating mesh nebulizers positioned 15 cm before the Y piece; (2) the use of continuous rather than breath-synchronous nebulization to allow the nebulization of high doses of CMS; (3) the use of specifically designed respiratory circuits with smooth inner surfaces and avoiding sharp angles to decrease turbulence and circuit deposition; (4) the use of specific ventilator settings to limit circuit and tracheobronchial impaction of aerosolized particles: volume controlled mode with constant inspiratory flow, tidal volume 8 mL/kg, respiratory frequency 12 to 15 bpm, inspiratory: expiratory ratio 50%, inspiratory pause 20% and positive end-expiratory pressure 5 to 10 cm H 2 O; (5) the administration of a short-acting sedative agent to ensure coordination between the patient and the ventilator;…”
Section: Administration and Dosing Of Nebulized Colistimethate Sodium 61 Technique Of Nebulizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 8 ] Western medicine routine treatment mainly uses antibiotics (penicillins, cephalosporins, macrolides, and aminoglycosides etc.) [ 12 21 ] and antiviral drugs (interferon and ribavirin). [ 22 25 ] However, the evaluation of their efficacy is not scientific and systematic.…”
Section: Introductionmentioning
confidence: 99%